Avaliação de métodos de preparo de amostras para a determinação de halogênios em plantas medicinais - Nascimento, Mariele Samuel do (2015)
In this work, four sample preparation methods were evaluated for further determination of halogens (F, Cl, Br e I) in medicinal plants. The evaluated sample preparation methods were microwave-induced combustion (MIC), microwave-assisted wet digestion (MAWD), microwave-assisted alkaline extraction (MAE) and alkaline extraction in open system (AE). The determination of F was performed by potentiometry using ion selective electrode (ISE) and ion chromatography (IC). Chlorine was determined by inductively coupled plasma optical emission spectrometry (ICP-OES) and Br and I were determined by inductively coupled plasma mass spectrometry (ICP-MS). In MIC, 100 mmol L-1 NH4OH was used as absorbing solution. In MAWD solutions of HNO3 (1, 4, 7 and 14.4 mol L-1) with H2O2 were used for decomposition of samples. It was observed an agreement with reference values better than 95% when 1 mol L-1 HNO3 was used. The alkaline extraction (MAE and AE) was performed using H2O, 0.11 mol L-1 NH4OH and 0.11 mol L-1 TMAH. In MAE, the variables studied were: volume of extractor medium (6 and 10 mL), temperature (90 and 240 °C) and extraction time (5 and 20 min). MAE and AE showed interference for F determination by ISE and IC. The accuracy of MIC and MAE methods was evaluated using certified reference materials (CRM). In MIC, accuracy between 90 and 97% for Cl, Br and I was observed. Further evaluation of the sample preparation methods (MAWD, MAE and AE) was performed for recovery of Br by the addition as KBr and CH3Br, considering that methyl bromide is used as fumigant in agricultural practices and can be a contaminant of Br in plants. The recovery of Br using KBr was better than 91% (MIC, MAWD, MAE and AE). However, the recovery of Br using methyl bromide was lower than 22% (MAE). Limits of detection lower than 15 μg g-1 (ISE) was obtained for all prepare methods evaluated.